Escape from harem: a women-empowered novel of the Mughal harem - Murugaiyan, Mohana Kala; Mani, Mani Mangai (AESS Publications, 2024)
This study endeavors to scrutinize the intricate roles of women within Mughal harems and their corresponding social hierarchies, with a particular focus on the pervasive mental and physical oppression endured by these women and their endeavors to reclaim their autonomy and individuality. Employing Michel Foucault’s conceptual framework of power within the context of new historicism, the narrative of Escape from Harem is meticulously examined to unravel the multifaceted dynamics inherent in harem life. Through an analytical lens, this study uncovers the entrenched power structures governing the harem environment, exposing the systematic marginalization and restriction of women within these secluded spaces. By delving into the diverse experiences of women from varied social backgrounds, exemplified by the protagonist Zeenat, the research underscores their tenacity and agency in navigating the constraints imposed upon them. Furthermore, this investigation underscores the profound significance of literature as a potent medium for social critique and advocacy, illustrating how narratives such as Escape from Harem serve as compelling instruments for challenging prevailing power dynamics and advocating for transformative societal change. This study not only enriches our comprehension of Mughal society but also underscores the enduring impact of literature in reflecting and shaping cultural norms and values.